2015
DOI: 10.1097/gox.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid and Sternum Fibroblasts Differ in Their Contraction Potential and Responses to Inflammatory Cytokines

Abstract: Background:Adverse skin scarring varies by anatomical site with, for example, presternal skin showing a greater hypertrophic response when compared with eyelid; such differences have traditionally been attributed to regional variations in skin tension, thickness, and Langer’s lines. Fibroblasts are the main cell implicated in fibrosis, and they too are known to show anatomical variation in their expression, differentiation, and intercellular interactions. We, therefore, investigated whether intrinsic differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The biopsy was mechanically dispersed, outgrown from the explant and established as a primary in vitro culture (Li et al, 2015). Monolayer cultures of fibroblasts were grown in T75 cm 2 vented flasks in Â1 DMEM (Sigma-Aldrich, Poole, UK) supplemented with 10% (v/v) FBS (Gibco, Paisley, UK), 1% (v/v) L-glutamine (Sigma-Aldrich) and 1% (v/v) penicillin-streptomycin-amphotericin B (Sigma-Aldrich).…”
Section: Free-floating Fibroblast-populated Collagen Lattice (Fpcl) Amentioning
confidence: 99%
“…The biopsy was mechanically dispersed, outgrown from the explant and established as a primary in vitro culture (Li et al, 2015). Monolayer cultures of fibroblasts were grown in T75 cm 2 vented flasks in Â1 DMEM (Sigma-Aldrich, Poole, UK) supplemented with 10% (v/v) FBS (Gibco, Paisley, UK), 1% (v/v) L-glutamine (Sigma-Aldrich) and 1% (v/v) penicillin-streptomycin-amphotericin B (Sigma-Aldrich).…”
Section: Free-floating Fibroblast-populated Collagen Lattice (Fpcl) Amentioning
confidence: 99%
“…However, while both control and GO orbital fibroblasts express αSMA, we found that macrophage-mediated stimulation of fibroblast contractility was not linked to αSMA expression; rather, macrophages stimulated actin dynamics in fibroblasts, with increased protrusive activity and actin polymerization. We have shown previously that such dynamic protrusive activity in 3D gels is sufficient to generate contractile force in primary human fibroblasts, and may represent an alternate pathway to the fibrotic phenotype 21,5456 . Consistent with this, macrophage-mediated contractility in orbital fibroblasts was not prevented by blocking TGF-β signalling, the classical upstream pathway mediating the acquisition of the myofibroblast phenotype 57 .…”
Section: Discussionmentioning
confidence: 93%
“…18,19 Myofibroblasts differentiate from fibroblasts in dermis and have intrinsic contractile properties imbued by alpha-actin filament bundles, though notably, the degree of fibroblast differentiation depends on wound location. 20 Because degree of fibroblast to myofibroblast differentiation and contractile forces are low in the periorbital area 21 and because MatriDerm suppress this fibroblast differentiation, 22 it is explainable that the use of STSG with a dermal substitute might be expected to produce comparable or better aesthetic results than FTSG in periorbital area.…”
Section: Discussionmentioning
confidence: 99%